The Impact of Pain and Family Stress on Children’s Sleep in a National Sample of Children with Chronic Illness - Bahulekar, Dhanashree R (East Carolina University, 2022)
Sleep problems represent one of the most common pediatric problems children face during their lives. Difficulties associated with sleep are visibly present across various populations of children with chronic illness. Additionally, children with chronic illness may experience difficulties with repeated or chronic pain due to the side effects of their illness. Parents may experience heightened stress levels while managing their child’s chronic illness. This study focused on determining factors that contribute to disruptive sleep patterns among children with asthma, epilepsy or seizure disorder, heart condition, or blood disorder. Parent-reported responses to questions about sleep, pain, aggravation, and coping from the National Survey of Children Health 2018-2019 were used for the present study. Results indicated a relationship between pain and sleep and caregiver stress and sleep. The relationship between caregiver stress and sleep was contingent on the child’s age. These findings suggest that pain and caregiver stress lead to poor sleep hygiene in children with chronic illnesses, which must be addressed given the importance of sleep in chronic illness management. Future research should examine different levels of pain in children, sleep problems in other chronic illness populations, and use measures with a consistent timeline.
Keywords: chronic illness; Children--Sleep; Chronically ill children; Pain in children; Stress (Psychology); Caregivers--Mental health; Parents of chronically ill children--Attitudes